The Strategy of the Tourism Office in Managing Tourist Areas on Pelabuhan Ratu Beach, Sukabumi Regency - Neng Alvi Hasanah; Tuah Nur; Dine Meigawati (Program Pascasarjana Universitas Negeri Makassar, 2023)
The Pelabuhan Ratu Beach area is a mainstay tourist spot for the people of Sukabumi Regency because it has a lot of interesting tourism potential. The purpose of this study is to determine the strategy of the Tourism Office in the management of tourist areas on Pelabuhan Ratu Beach. The problems identified related to its management are still not optimal in increasing the capacity of tourism resources and maintenance/procurement/rehabilitation of facilities and infrastructure so that the number of tourists coming to the Pelabuhan Ratu Beach area will decrease. This research uses qualitative research methods with a descriptive approach. and data collection techniques, namely observation, interviews and documentation. Then the data analysis stage by reducing data, presenting data and drawing conclusions. The results of this study are measured by three dimensions proposed by Dess & Miller, namely goals, policy, and plans. The results in this study show that in increasing tourist visits, related agencies are improving the arrangement of tourist areas around Pelabuhan Ratu Beach to make it even better. Such as paying attention to the 4A aspects (attaraction, accessbility, amenity, and ancilliary and improving tourism destination marketing strategies. Meanwhile, in increasing the capacity of tourism resources, monitoring and evaluation are carried out by conducting trainings. Then plans in the procurement/ maintenance/rehabilitation of facilities and infrastructure, namely by transferring and eliminating facilities and infrastructure.